Learning, teaching, and community : contributions of situated and participatory approaches to educational innovation - Schecter, Sandra R.; Pease-Alvarez, Lucinda (Mahwah, N.J. : L. Erlbaum, 2005)
"This volume brings together established and new scholarly voices to explore how participatory and situated approaches to learning can contribute to educational innovation. The contributors' critical examinations of educational programming and engagements provide insights into how educators, youth, families, and community members understand and enact their commitments to diversity and equitable access. Collectively, these essays complicate notions of community, alerting readers to ways in which community can be constructed other than in geographical and ethnoracial terms - as alliances and collaborations of individuals joining together to accomplish or negotiate shared agendas. The focus on agency combined with social context, a dialectic to which all of the authors speak, enlarges and invigorates our sense of what is pedagogically possible in societies characterized by diversity and flux." "Teaching, Learning, and Community: Contributions of Situated and Participatory Approaches to Educational Innovation is a timely text ideally suited for courses focused on teacher education and development, informal learning, equity and education, multilingual and multicultural education, language and culture, educational foundations, and school reform/educational restructuring, and will be equally of interest to faculty, researchers, and professionals in these areas."--BOOK JACKET.
Linking pedagogy to communities -- Professional learning for diversity -- Learning in community (and community in learning).
Includes bibliographical references and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Multicultural education -- Canada -- Case studies; Multicultural education -- United States -- Case studies; Community and school -- United States -- Case studies; Community and school -- Canada -- Case studies; Educational innovations -- United States -- Case studies; Educational innovations -- Canada -- Case studies; Electronic books